Cinema muto - Kercheval, Jesse Lee (Crab Orchard award series in poetry., 2009)
In Cinema Muto, Jesse Lee Kercheval examines the enduring themes of time, mortality, and love as revealed through the power of silent film. Following the ten days of the annual Le Giornate del Cinema Muto in Italy, this collection of ekphrastic poems are love letters to the evocative power of silent cinema. Kercheval's poems elegantly capture the allure of these rare films, which compel hundreds of pilgrims from around the world-from scholars and archivists, to artists and connoisseurs-to flock to Italy each autumn. Cinema Muto celebrates the flickering tales.